2021
DOI: 10.1093/eurjcn/zvab056
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing health-related quality of life of patients with a left ventricular assist device: a systematic review and thematic synthesis

Abstract: Aims Left ventricular assist devices (LVADs) are increasingly being used in the treatment of advanced heart failure. Left ventricular assist device patients frequently report improvements in health-related quality of life (HRQOL) post-implantation. However, HRQOL varies over time and between patients, which can be explained by patient-related and environmental factors, as individual studies suggest. This review aims to synthesize qualitative evidence on factors influencing HRQOL of LVAD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 52 publications
2
11
0
4
Order By: Relevance
“…The influence of additional psychosocial factors like health literacy, mental illness, adherence behaviors, and substance abuse is more subjective. Each of these factors has been shown to increase the risk of readmission after implant or has been associated with an increased risk of having an adverse LVAD event [ 30 , 35 , 36 ]. Although these factors do not disqualify an individual from receiving an LVAD, their presence and severity are evaluated carefully to determine whether LVAD implantation is likely to be more beneficial than harmful, and to plan appropriate care both prior to and after the LVAD implantation.…”
Section: Patient Management and Optimizationmentioning
confidence: 99%
“…The influence of additional psychosocial factors like health literacy, mental illness, adherence behaviors, and substance abuse is more subjective. Each of these factors has been shown to increase the risk of readmission after implant or has been associated with an increased risk of having an adverse LVAD event [ 30 , 35 , 36 ]. Although these factors do not disqualify an individual from receiving an LVAD, their presence and severity are evaluated carefully to determine whether LVAD implantation is likely to be more beneficial than harmful, and to plan appropriate care both prior to and after the LVAD implantation.…”
Section: Patient Management and Optimizationmentioning
confidence: 99%
“…This complication can appear immediately after surgery or in the next days. Despite the best efforts, mortality rates reach up to 29% [29][30][31][32] . The challenges of heart transplantations are vast, such as the immunosuppressive protocol, antibiotic and antiviral protocols, antiplatelet/anticoagulation protocol, multi-organ impact and eligibility criterion.…”
Section: A B Cmentioning
confidence: 99%
“…8,9 LVADs may entail psychological burdens: Fear of complications and dependence on technology are recurring concerns due to visible extracorporeal components. 6,7,10 The patients' ability to cope with these challenges and adjust to the situation is crucial for psychosocial outcomes 11 and can be investigated using the transactional model of stress and coping (TMSC). 12,13 The TMSC distinguishes between two processes, cognitive appraisal and coping.…”
Section: Introductionmentioning
confidence: 99%
“…16 Further reviews demonstrated how the adaptation process and individual quality of life are influenced by how patients deal with these challenges and their available resources. 11,17 Besides this theoretical framework, no original study examined the various burdens and coping processes in DT patients, which better understanding may provide improved targeted support. Therefore, this study aims to explore psychological burden, coping resources, and strategies from the perspective of DT patients living with an LVAD over a time span of 3 months to more than 10 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation